Changes in family formation among Turkish and Maroccan women in Belgium - Lodewijckx, Edith; Page, Hilary; Schoenmaeckers, Ronald (Brussel: Centrum voor Bevolkings- en Gezinsstudiën, 1995)
"Edith Lodewijckx; Hilary Page; Ronald Schoenmaeckers Fonds Suzan Daniel (FSD)"